GAYA BAHASA SINDIRAN DAN PERBANDINGAN PADA STATUS TWITTER SUJIWO TEJO - Nurul Arifiyani; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2015)
This research aims to describe types of satire style, comparison style, function language style, and meaning of language style on the Sujiwo Tejo’s status at Twitter. This research type is qualitative descriptive. Data is sentenced usage on the Sujiwo Tejo’s status at Twitter that consist of satire style, comparison style, the function of style, and meaning of style. Data is obtained from the data source that sentences usage in the Sujiwo Tejo’s status on Twitter. Data collection technique is scrutinizing method, while the advanced technique is free to scrutinize method involve talk and note. Data analysis method is a unified autograph method, while the basic method is matching of sorting method certain element. Presenting result method of data analysis by informal technique. Result of the research on the Sujiwo Tejo’s status on Twitter is as follows: (1) kind of satire styles on the Sujiwo Tejo’s status at Twitter includes: (a) irony, (b) word game, (c) sarcasm, (d) cynicism, (e) satire, (2) comparison styles on the Sujiwo Tejo’s status at Twitter includes: (a) allusion, (b) antonomasia, (c) hyperbola, (d) litotes, (e) personification, (f) a simile, (i) synecdoche totem pro parte, (3) function of language style on the Sujiwo Tejo’s status at Twitter consists of : language style which is used to create mood, (b) language style is used to ensure the reader, (c) language style is used to strengthen effect toward conveyed idea, (4) meaning of language style on the Sujiwo Tejo’s status at Twitter consists of: (a) similarity of meaning from both items, (b) proximity of meaning between both items, (c) implementation of one meaning with other meaning implementation.